ISOLASI DAN IDENTIFIKASI GLIKOSIDA FLAVONOID BIOAKTIF DARI SYZYGIUM JAMBOS DAN AKTIVITAS PENGHAMBAT ENZIM α-GLUKOSIDASE - Meilani, Lani; Nor, Islan; Insanu, Muhamad (School of Pharmacy Institut Teknologi Bandung, 2024)
Diabetes has grown into a demanding global public health problem, with generally 537 million individuals afflicted worldwide. Without appropriate intervention, the risk of developing chronic complications increases. One of the practical actions for controlling type 2 diabetes mellitus is suppressing carbohydrate-hydrolyzing enzymes such as α-glucosidase. Syzygium jambos has a long history as a traditional medicine. It's commonly used to treat diabetes, rheumatism, inflammatory pain, and as a diuretic. This study aimed to investigate the α-glucosidase inhibitory properties of S. jambos leaves and their isolated compounds. Ethanol was used as the solvent for maceration, followed by fractionation using liquid-liquid extraction, vacuum liquid chromatography, column chromatography, and radial chromatography. The isolated compounds were identified using thin-layer chromatography (TLC), TLC densitometry, shifting reagents, infrared (IR) spectroscopy, mass spectrometry, and nuclear magnetic resonance (NMR) spectrometry. The ethyl acetate fraction presented the most potent activity of α-glucosidase inhibitory, with an IC50 value of 0.31 ± 0.01 µg/mL, exceeding the acarbose as positive control (IC50 62.86 ± 1.24 µg/mL). Two flavonoid glycosides, quercetin 3-O-xylosyl-(1→2)-rhamnoside and myricetin 3-O-xylosyl-(1→2)-rhamnoside, were identified inside this fraction, with IC50 values of 65.63 ± 1.36 µg/mL and 188.96 ± 2.85 µg/mL, respectively. These findings suggest that S. jambos has potential as a natural source for developing dietary supplements to control hyperglycemia affiliated with type 2 diabetes mellitus.